Fruit damage during transportation - Bardaie, Mohd Zohadie; Hitam, Bahanurdin (Penerbit Universiti Pertanian Malaysia, 1981)
Damage during transportation is a problem with fruits which are for fresh consumption and processing. This damage is due to repeated forces of vibration on the fruit. The intensity and duration of vibration will determine the severity of damage. There are a number of factors which are involved in the problem, namely a) the vibrating characteristics of the fruit species, b) the depth to which the container is filled, c) the tightness of fill, d) the type of suspension system used on the transportation trucks and e) the magnitude of forced vibration from the roadbed. these factors are closely interrelated to each other. they are discussed in this paper, and those which are easily controllable for reducing the fruit damage during transportation are identified.